Hungarian Monitoring, 26 January 1988 . [Magyar rádiófigyelő], 1988. január 26 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - On Kohl's Prague schedule - American President's State of the Union address - On the USSR's Middle Eastern policy - GDR authorities step up against opponents Domestic Affairs: - János Kádár and Károly Németh send telegram to Ceauşescu on his 70th birthday - Radio diary on foreign affairs with guest Mátyás Szűrös - Hungarian delegation at the first AIDS world congress - Dangerous waste transports in Hungary - Social and health situation of the elderly - Academic conference on the origins of the Csangos - Budapest Council discusses this year's budget and improvements Economy: - Press conference on Hungarian National Bank activities Külpolitika - Kohl prágai programjáról - Az amerikai elnök jelentése az unió helyzetéről - A Szovjetunió közel-keleti politikájáról - NDK hatóságok fellépése ellenzékiekkel szemben Belpolitika: - Kádár János és Németh Károly táviratban üdvözli Ceauşescut 70. születésnapja alkalmából - Rádiónapló a külpolitikáról: a műsor vendége Szűrös Mátyás - Magyar küldöttség az első AIDS világkongresszuson - A veszélyes hulladékok szállításának hazai helyzete - Az időskorúak szociális és egészségügyi helyzete - Tudományos tanácskozás a csángók eredetéről - A Főváros Tanács az idei költségvetésről és fejlesztésekről tárgyal Gazdaság: - Sajtótájékoztató az MNB tevékenységéről